(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Placental infarction is a condition where placental tissue dies due to poor blood flow from the mother. This is often linked to maternal health issues like high blood pressure, diabetes, and blood clotting disorders. It can cause problems like restricted fetal growth and stillbirth. When infarctions are widespread or multiple, outcomes for mother and baby are often poor. Small, isolated infarctions might not be significant, but there’s limited evidence to confirm this. • Case: We present a 24 -year-old gravida 2 para 1+0 woman with an uneventful pregnancy, normal fetal growth, and spontaneous vaginal delivery at term. Placental examination revealed a single, well-demarcatedinfarct 5*5 cm in greatest There were no maternal risk factors (hypertension, preexisting diabetes, thrombophilia) and no neonatal complications. • Conclusion:This case highlights that isolated small placental infarcts may occur in otherwise normal pregnancies without adverse outcomes, underlining the importance of correlating placental findings with the clinical context.